Orientation for the Development of Superior Lecturers in Facing the Era of Industrial Revolution 4.0 - Indrawati Indrawati (STAI Hubbulwathan Duri, 2021)
This study wants to explain the development of lecturers in performing tridharma and strategic orientation that can be done to achieve superior resources. Management human resources should be the focus of the college. The quality of higher education is largely determined by the quality of human resources, namely lecturers and educational staff. Likewise, the quality of graduates will be determined by the quality of the lecturers. Therefore, universities are required to move quickly in anticipating and taking strategic steps to manage human resources so that the quality standards of lecturers and education personnel can be increased which in turn can respond to the needs in the era of the industrial revolution 4.0. The superior parameters used in this study refer to the human resource indicators in the BAN-PT accreditation instrument. The research method used a descriptive qualitative approach by conducting literature studies, interviews, and surveys. The results showed that the efforts made by the university partly showed good results, but there are still indicators that still need to organize a strategy to improve the quality standards of lecturers and education staff and prepare human resources for the era of the industrial revolution 4.0.